La production de la céramique antique dans la région de Salakta et Ksour Essef (Tunisie) - Nacef, Jihen, (Roman and late antique Mediterranean pottery ;, 2015)
This publication provides information on the ceramic production (amphorae, cooking and coarse wares, ceramic building materials) of Salakta and the Ksour Essef district, in the Sahel region of Tunisia, from the 3rd century BC to the 7th century AD. This book deals with the history and the archaeology of Sullecthum/Salakta, the typology of the ceramic production (mainly amphorae), the chronology and the location of the workshops, the amphora stamps and contents, the distribution in the Mediterranean, and the organisation of production and trade.